PENGARUH KONDISI LINGKUNGAN DI DALAM KANDANG ANTARA KANDANG OPEN HOUSE DAN SEMI CLOSED HOUSE TERHADAP PERFORMA AYAM BROILER DI PT BUSS SUKABUMI - Ramadhani, Mega Destri; Ismoyowati, Ismoyowati; Setianto, Novie Andri (ANGON: Journal of Animal Science and Technology, 2024)
The internship entitled "The Effect of Environmental Conditions in Cages Between Open House Cages and Semi-Closed Houses on the Performance of Broiler Chickens on the Performance of Broiler Chickens at PT BUSS Sukabumi" was held on September 15 2021 to December 25 2021, at PT. Berkat Unggas Sehat Sejahtera, Sukabumi, West Java. The purpose of this internship is to analyze the influence of environmental conditions in the cage between open house and semi closed house cages. The method used in this internship is carrying out broiler maintenance activities with a focus on observing the environmental conditions of the cage and the performance of broiler chickens. The target of the internship is broiler chicken farm at PT. Berkat Unggas Sehat Sejahtera. The material used in open house cages was Cobb strain chickens with a total of 6500 population while for semi closed house cages using Rose strain chickens with a population of 12,103 population. The observation took place at PT. Berkat Unggas Sehat Sejahtera. The variables observed were body weight, body weight gain, mortality, feed conversion ratio (FCR), and IP in chickens kept in open house and semi closed house cages. Performance in the open house cage in the fourth week resulted in a body weight of 1530 g with a PBB of 573 g with a mortality rate of 4.75%, then the FCR obtained was 1.48, and the IP was 350. Performance in the semi closed house cage in the fourth week resulted in body weight 1552 g with PBB of 578 g, the mortality rate was 4.34%, then the FCR was 1.43, and the IP was 372. When compared to the open house cage, the temperature in the semi-closed house cage is more conducive to broiler chicken growth. Broiler chickens perform differently in open-house and semi-closed-house cages due to variations in temperature and humidity. The performance of semi-closed house cages is superior to that of open house cages.